Cross-Resistance to Abiraterone and Enzalutamide in Castration Resistance Prostate Cancer Cellular Models Is Mediated by AR Transcriptional Reactivation - Simon, Iris; Perales, Sonia; Casado-Medina, Laura; Rodríguez-Martínez, Alba; Garrido-Navas, M. Carmen; Puche-Sanz, Ignacio; Diaz-Mochon, Juan J.; Alaminos, Clara; Lupiañez, Pablo; Lorente, José Antonio; Serrano, M. José; Real, Pedro J. (Cancers, 2021)
Androgen deprivation therapy (ADT) and novel hormonal agents (NHAs) (Abiraterone and Enzalutamide) are the goal standard for metastatic prostate cancer (PCa) treatment. Although ADT is initially effective, a subsequent castration resistance status (CRPC) is commonly developed. The expression of androgen receptor (AR) alternative splicing isoforms (AR‐V7 and AR‐V9) has been associated to CRPC. However, resistance mechanisms to novel NHAs are not yet well understood. Androgen‐dependent PCa cell lines were used to generate resistant models to ADT only or in combination with Abiraterone and/or Enzalutamide (concomitant models). Functional and genetic analyses were performed for each resistance model by real‐time cell monitoring assays, flow cytometry and RT‐qPCR. In androgen‐dependent PCa cells, the administration of Abiraterone and/or Enzalutamide as first‐line treatment involved a critical inhibition of AR activity associated with a significant cell growth inhibition. Genetic analyses on ADT‐resistant PCa cell lines showed that the CRPC phenotype was accompanied by overexpression of AR full‐length and AR target genes, but not necessarily AR‐V7 and/or AR‐V9 isoforms. These ADT resistant cell lines showed higher proliferation rates, migration and invasion abilities. Importantly, ADT resistance induced cross‐resistance to Abiraterone and/or Enzalutamide. Similarly, concomitant models possessed an elevated expression of AR full‐length and proliferation rates and acquired cross‐resistance to its alternative NHA as second‐ line treatment.
Keywords: abiraterone; androgen receptor; AR‐V7; AR‐V9; Castration resistant prostate cancer; cross‐resistance; enzalutamide; novel hormonal agents; transcriptional regulation; Scopus; WOS(2)